High altitude adaptation: Genetic perspectives - Stobdan, T.; Karar, J.; Qadar Pasha, M. A. (High Altitude Medicine & Biology, 2008)
The goal of this review is to highlight the underlying genetics that may explain complex traits associated with high altitude adaptation. The review covers the traditional candidate gene approach for identifying molecular variants having a functional role and associating with high altitude adaptation and disorders. We review some of the salient features of these candidate genes, debating their potential role in high altitude fitness. The advancement in high-throughput techniques in molecular genetics and the availability of large-scale catalogs of genetic variation in the public domain have provided a better platform for genome-wide scans for identifying genetic components for many traits. Current techniques such as whole-genome scans, admixture mapping using powerful tag SNPs, and the vast data available from human genome sequencing and the HapMap project may aid in a comprehensive understanding of genomic patterns of high altitude adaptation as well as disease-related research.